2018
DOI: 10.1002/anie.201713158
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Specific Studies of Nucleosome Interactions by Solid‐State NMR Spectroscopy

Abstract: Chromatin function depends on a dense network of interactions between nucleosomes and a wide range of proteins. A detailed description of these protein–nucleosome interactions is required to reach a full molecular understanding of chromatin function in both genetics and epigenetics. Herein, we show that the structure, dynamics, and interactions of nucleosomes can be interrogated in a residue‐specific manner by using state‐of‐the‐art solid‐state NMR spectroscopy. Using sedimented nucleosomes, high‐resolution sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 50 publications
6
47
0
Order By: Relevance
“…Solid‐state NMR (SSNMR) has been emerging as a powerful technique for biomolecular structure and dynamics characterization and has been successfully employed for studying various systems . In a recent study, proton‐detected SSNMR experiments were performed on the NCP and NCP:LANA complex, which included 2 H, 13 C, 15 N‐labeled H2A . This study determined the H2A secondary structure and confirmed the interface structure between the nucleosome and LANA previously determined by X‐ray crystallography .…”
Section: Figuresupporting
confidence: 68%
“…Solid‐state NMR (SSNMR) has been emerging as a powerful technique for biomolecular structure and dynamics characterization and has been successfully employed for studying various systems . In a recent study, proton‐detected SSNMR experiments were performed on the NCP and NCP:LANA complex, which included 2 H, 13 C, 15 N‐labeled H2A . This study determined the H2A secondary structure and confirmed the interface structure between the nucleosome and LANA previously determined by X‐ray crystallography .…”
Section: Figuresupporting
confidence: 68%
“…[7] In ar ecent study, proton-detected SSNMR experiments were performed on the NCP and NCP:LANAc omplex, which included 2 H, 13 C, 15 Nlabeled H2A. [8] This study determined the H2A secondary structure and confirmed the interface structure between the nucleosome and LANAp reviously determined by X-ray crystallography. [9] Thei nherent plasticity of the central HO enables the NCP serving as as tructural scaffold in the nucleosome compaction and facilitating DNA-templated processes.…”
mentioning
confidence: 76%
“…This is for some of these systems probably a consequence of oligomerization that has been induced by the high protein concentrations (Bertini et al, 2013;Fragai et al, 2013). Protein-protein complexes were studied by co-sedimentation (Gardiennet et al, 2016;Xiang et al, 2018) and protein-ligand complexes by sedimentation with the respective ligand (e.g. nucleic acids) directly into the NMR rotor (Wiegand et al, 2016a;Kaur et al, 2018;Stöppler et al, 2018;Lacabanne et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%